2015
DOI: 10.1155/2015/787890
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey for Avian Influenza in Turkeys in Three States of Southwest Nigeria

Abstract: Since the first outbreak of avian influenza (AI) in Nigeria in 2006, there has been continuous monitoring of the disease in chickens with little attention given to turkeys. As part of on-going surveillance for AI in southwest Nigeria, we used a competitive ELISA to detect anti-AI virus antibodies in 520 turkey sera obtained from poultry farms in Oyo, Osun, and Ondo states while haemagglutination inhibiting antibodies against low pathogenic AI viruses (LPAIVs) were detected using H3N8 and H5N2 subtype-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…H9N2, H3N8, H5N2, H7N7 and H6N2 LPAI viruses were also detected in domestic poultry. For example, H9N2 LPAI virus detected in Burkina Faso [ 91 ] and Ghana [ 41 ] and H6N2 LPAI virus in South Africa [ 92 , 93 ] were from symptomatic poultry with signs of respiratory distress, decreased egg production and increased mortality, while in Kenya [ 64 ] and Nigeria [ 78 , 94 ] viruses with subtypes H9N2, H7N7, H5N2 and H3N8 were detected in asymptomatic birds. Moreover, mixed infection of H3N8 and H5N2 LPAI viruses was detected in apparently health turkeys ( Meleagris Spp.)…”
Section: Resultsmentioning
confidence: 99%
“…H9N2, H3N8, H5N2, H7N7 and H6N2 LPAI viruses were also detected in domestic poultry. For example, H9N2 LPAI virus detected in Burkina Faso [ 91 ] and Ghana [ 41 ] and H6N2 LPAI virus in South Africa [ 92 , 93 ] were from symptomatic poultry with signs of respiratory distress, decreased egg production and increased mortality, while in Kenya [ 64 ] and Nigeria [ 78 , 94 ] viruses with subtypes H9N2, H7N7, H5N2 and H3N8 were detected in asymptomatic birds. Moreover, mixed infection of H3N8 and H5N2 LPAI viruses was detected in apparently health turkeys ( Meleagris Spp.)…”
Section: Resultsmentioning
confidence: 99%
“…Considering that AI viruses have been reported to impact negatively on food supply and the economy through their effects on the poultry industry (Peiris et al, 2007), flock surveillance can help establish the epidemiological characteristics of AIV infection that would inform development of prevention and control strategies, especially in countries like Nigeria where vaccination against AI is currently prohibited. As part of routine screening for AIVs in southwest Nigeria (Aiki-Raji et al, 2015; Oluwayelu et al, 2015), serologic and molecular surveillance for LPAIVs was conducted in birds from commercial breeder and layer flocks in Oyo state. It has been reported that serologic screening provides insight into the infection history of an animal's entire life (CouacyHymann et al, 2012) while RT-PCR detection of the shedding of viral RNA is often performed to monitor the current influenza status in birds (Wallerström et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A speculative association might be drawn, due to the agreement of the subtype antibodies detected in our study, and the human influenza A virus prevalent in 2016 in Brazil, in both cases the H1 subtype (WHO, 2016). However, it could be postulated that a low interspecies transmission may take place in Belo Horizonte and Santa Maria regions, considering the predominant type of exploitation, characterized by A serological study in Nigeria in 2016, conducted after a large scale outbreak, with hundreds of affected properties and massive economic impact, has shown a total prevalence of 4,4% by ELISA and HI (Oluwayelu et al, 2015) for H3N8 and H5N2 subtypes, with antibody titers to subtype H1 ranging from 1:8 to 1:2,048. Nigeria, as well as other parts of Africa, has been affected by the Eurasian outbreaks of highly pathogenic AIV (OIE, 2017).…”
Section: Discussionmentioning
confidence: 99%